2015
DOI: 10.1186/s12913-015-0950-9
|View full text |Cite
|
Sign up to set email alerts
|

The number of discharge medications predicts thirty-day hospital readmission: a cohort study

Abstract: BackgroundHospital readmission occurs often and is difficult to predict. Polypharmacy has been identified as a potential risk factor for hospital readmission. However, the overall impact of the number of discharge medications on hospital readmission is still undefined.MethodsTo determine whether the number of discharge medications is predictive of thirty-day readmission using a retrospective cohort study design performed at Barnes-Jewish Hospital from January 15, 2013 to May 9, 2013. The primary outcome assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
82
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 16 publications
4
82
2
Order By: Relevance
“…The attendant risks of taking many medications are well described in the Geriatrics literature, with known associations with a number of adverse outcomes, including falls, disability, and hospitalizations . Consequently, there is an inherent tension between this observation and providing guideline‐concordant care to adults with HF, which frequently includes concurrently prescribing various medications for HF, as well as for other common comorbid cardiovascular and noncardiovascular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The attendant risks of taking many medications are well described in the Geriatrics literature, with known associations with a number of adverse outcomes, including falls, disability, and hospitalizations . Consequently, there is an inherent tension between this observation and providing guideline‐concordant care to adults with HF, which frequently includes concurrently prescribing various medications for HF, as well as for other common comorbid cardiovascular and noncardiovascular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in the number of medications as well as polypharmacy have been recognized as the most important risk factors for adverse drug reactions linked to rehospitalization. . Picker et al found that the number of discharge medications was significantly associated with the risk of hospital readmission within 30 days .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have identified age, race, having a regular health care provider, major surgery, medical comorbidities, length of hospital stay, previous admissions in the last year, failure to transfer important information to the outpatient setting, discharging patients too soon, the number of medications at discharge, and many other risk factors for hospital readmission within 30 days (Auerbach et al, 2016; Picker et al, 2015; Hasan et al, 2010; Silverstein et al, 2008). Despite identifying with these risk factors, healthcare providers have poor accuracy in predicting which patients are at high risk of hospital readmission without a risk assessment tool (Allaudeen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%